Optimization of extraction total flavonoids and marker compounds from Passiflora foetida L. using response surface methodology - Nguyen , Huu Tien; Dang , Tran Minh Xuan; Tran , Huu Dung (Tạp chí Y Dược Huế, 2025)
Background: Currently, a wide range of products derived from Passiflora foetida are commercially available; however, the lack of standardized extraction procedures has led to inconsistencies in product quality. Objectives: To develop an optimized extraction process for total flavonoid content and marker compounds from Passiflora foetida using a conventional extraction method. Materials and methods: The material studied is the leaves and stems of Passiflora foetida. The extraction conditions for vitexin, isovitexin, and total flavonoid content from Passiflora foetida were investigated and optimized using response surface methodology. Results: The optimal extraction conditions were determined using a central composite design, with 56% ethanol concentration, a solvent-to-solid ratio of 17.54 mL/g, and a soaking time of 3 hours. Under these conditions, the extraction yields were 0.0644 ± 0.0005% for vitexin, 0.00180 ± 0.00003% for isovitexin, and 1.385 ± 0.056% for total flavonoids. Conclusion: An optimized extraction process for bioactive compounds from P. foetida using percolation has been successfully developed.